Autonomous, Distributed Parking Lot Vacancy Management Using Intervehicle Communication. (21st July 2014) - Yamashita, Shohei; Takami, Kazumasa
Abstract : We have developed a method of managing vacancy information of a large parking lot in a distributed manner using only intervehicle communication. A group of parking spaces is defined as a cluster. Vacancy information of a cluster is managed by a vehicle in it. This vehicle is called a cluster head. The proposed method generates a communication path topology between cluster heads. The topology is a tree structure with the cluster head of the cluster nearest to the parking lot entrance as the root node. Cluster heads are ranked in order of the number of vacant spaces and the distance to the shop entrance. The vehicle entering the parking lot collects vacancy information of clusters. This information is transmitted along the tree structure from the lowest ranking cluster head. We have developed a simulation model for a parking lot that can accommodate nearly 1, 000 vehicles and used it to evaluate the proposed method. We have confirmed that the proposed method generates less communication traffic and enables the vehicle entering a parking lot to collect vacancy information about the area near the shop entrance with a higher probability and in a shorter time.